EP542 Computer adaptive testing discriminates early recovery after robotic surgery in women with early-stage endometrial cancer. (1st November 2019) - Jørgensen, SL; Mogensen, O; Petersen, MA; Wu, CS; Jensen, PT
Abstract : Introduction/Background: Knowledge on the individual recovery after robotic surgery for endometrial cancer (EC) is sparse but important for optimisation of pre-operative information and for post-operative supportive care. Generic questionnaires measuring quality-of-life are challenged by the diversity of these women, ranging from women who are part of the active workforce in their thirties to retired women in their nineties. The European Organisation of Research and Treatment of Cancer Computer Adaptive Test Core questionnaire (EORTC CAT Core) provides individualised measurements. Methodology: 94 consecutive women who underwent robotic minimally invasive surgery for early-stage EC at Odense University Hospital in Denmark were included. The EORTC CAT Core was distributed pre-operatively and every week during the first post-operative month. Repeated measures models were fitted for four domains; physical functioning, role function, fatigue, and pain. Each model was tested for impact of age, ASA score, minor/major surgery, and the individual baseline scores (poorest, intermediate, best). A hypothesis of individual complete recovery of physical health to baseline levels within three post-surgical weeks was evaluated. Results: Women with the lowest physical and role functions, and the highest fatigue and pain levels at baseline recovered within three weeks. Women with the highest physical health before surgery did not reach their individual baseline within the first post-operative month but had the most favorable domain-scores three weeks post-operatively. Conclusion: The individual woman´s baseline score of physical health is predictive for her postoperative recovery following robotic minimally invasive surgery for early-stage endometrial cancer. Recovery to the individual offset is prolonged in women with the best physical health. The EORTC CAT Core may be a valuable tool for individualised pre-operative information and supportive care during surveillance. Disclosure: Nothing to disclose.